Dietary diversity and cognitive performance in older adults: a systematic review - Sorayya Kheirouri; Hamed Alizadeh (BMC Neurology)
Abstract Background and objective Promoting dietary diversity (DD), which refers to the variety or the number of different food groups that people eat over the time given, is important for brain health maintenance and may be beneficial for inhibiting neurodegenerative diseases. This research aimed to review the literature and summarize research evidence for achieving an inclusive estimate concerning the relationship between DD and cognitive function in adults. Methods We systematically queried the databases of PubMed, Web of Science, and Google Scholar, without imposing any date restrictions, up to June 2024 to identify original literature that sheds light on the intricate relationship between DD and cognitive function. Employing rigorous criteria, we meticulously screened studies, eliminating duplicates or those unrelated to our focus. Subsequently, we critically evaluated the findings from the selected studies, descriptively summarizing them. Additionally, we engaged in an in-depth exploration of potential mechanistic pathways linking DD to cognitive performance. Results Of the 388 citations obtained, 23 articles were included in the final review. All the studies reported a positive association between DD score and cognitive functioning and indicated that higher DD was accompanied by good memory (n = 3) and lower risk of cognitive decline (n = 19), dementia (n = 3), and Alzheimer’s disease (n = 1). Conclusion The results indicate that sustaining a diverse diet among older people may help maintain cognitive functioning. Dietary diversity represents a promising clinical avenue for mitigating cognitive decline associated with diverse brain disorders, potentially preventing or attenuating deterioration.